2021
DOI: 10.1021/acschembio.1c00393
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Sphingolipid Metabolism Pathways during Phagosomal Maturation

Abstract: Phagocytosis is an important physiological process, which, in higher organisms, is a means of fighting infections and clearing cellular debris. During phagocytosis, detrimental foreign particles (e.g. pathogens and apoptotic cells) are engulfed by phagocytes (e.g. macrophages), enclosed in membrane-bound vesicles called phagosomes, and transported to the lysosome for eventual detoxification. During this well-choreographed process, the nascent phagosome (also called early phagosome, EP) undergoes a series of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…It is generally accepted, for example, that ceramidases play significant roles in regulating ceramide and sphingosine concentrations in cellular membranes [ 90 , 91 ]. Ceramides contribute mainly, but not exclusively, to the bilayers of MAM, ER, and Golgi [ 92 ]; for example, even in late phagosomes, glucosylceramides formed by glucosylceramide synthase (GCase) and UDP glucose are elevated for ceramide processing [ 93 ]. A generic signature binding sequence, VAMTLGQIYY, for sphingomyelin [ 94 , 95 , 96 ] (structure in Figure 2 B), has been identified within the TM helix of the Golgi coat protein, COPI p24 [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted, for example, that ceramidases play significant roles in regulating ceramide and sphingosine concentrations in cellular membranes [ 90 , 91 ]. Ceramides contribute mainly, but not exclusively, to the bilayers of MAM, ER, and Golgi [ 92 ]; for example, even in late phagosomes, glucosylceramides formed by glucosylceramide synthase (GCase) and UDP glucose are elevated for ceramide processing [ 93 ]. A generic signature binding sequence, VAMTLGQIYY, for sphingomyelin [ 94 , 95 , 96 ] (structure in Figure 2 B), has been identified within the TM helix of the Golgi coat protein, COPI p24 [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phagocytic and antigen‐presenting functions of MNPs are known to rely on sphingolipid metabolism [ 44 , 45 ]. The accumulation of ceramide in the phagosomes of MNPs has been reported to promote phagosomal maturation [ 46 ]. Indeed, a large body of studies have shown that sphingolipid metabolism could drive the migration, activation, and polarization of monocytes/macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of phagocytosis with quantitative lipidomics during the process of phagosomal maturation revealed that early phagosomes have enhanced activity of neutral ceramidase compared to CerS under neutral (pH 7.0) conditions, resulting in decreased ceramide levels. However, ceramides and glucosylceramides with long hydrocarbon chains (16:0, 18:0, 20:0, 22:0, and 24:0 but not 12:0 and 14:0) are gradually enriched on mature phagosomes of Raw264.7 cells, a murine macrophage cell line, with enhanced glucosylceramide synthase (GCS) activity, while sphingosines and the expression/activity of CerS2 are decreased 96 . During phagosomal maturation, the levels of sphingomyelin and C1P are comparable in early and late phagosomes, but activation of CERK and C1P can facilitate Fc receptor-mediated phagocytosis, collectively implying the delicate roles of sphingolipids in macrophage function 82 , 96 .…”
Section: Sphingolipids As Warning Molecules and Modulators Of The Inn...mentioning
confidence: 99%
“…However, ceramides and glucosylceramides with long hydrocarbon chains (16:0, 18:0, 20:0, 22:0, and 24:0 but not 12:0 and 14:0) are gradually enriched on mature phagosomes of Raw264.7 cells, a murine macrophage cell line, with enhanced glucosylceramide synthase (GCS) activity, while sphingosines and the expression/activity of CerS2 are decreased 96 . During phagosomal maturation, the levels of sphingomyelin and C1P are comparable in early and late phagosomes, but activation of CERK and C1P can facilitate Fc receptor-mediated phagocytosis, collectively implying the delicate roles of sphingolipids in macrophage function 82 , 96 . Although some bacteria and hosts have evolved to live together by symbiosis, other bacteria called pathogens have evolved to exploit and hijack host metabolites for their own purposes 53 , 62 .…”
Section: Sphingolipids As Warning Molecules and Modulators Of The Inn...mentioning
confidence: 99%
See 1 more Smart Citation